Comparative Analysis of Inherent Risk, Risk Management Quality and Risk Across Eight Risk Types at PT Bank Maluku Malut - Alend Talla; Zahra; Sari Tamayani Tjio (Yayasan Ilomata, 2026)
This study aims to analyze and compare inherent risk, risk management quality, and residual risk across eight types of risk at PT Bank Maluku Malut during the period 2022–2024. This research employs a descriptive-quantitative method with a comparative approach, utilizing secondary data derived from quarterly and annual risk profile reports. The results indicate that the bank’s overall risk profile was categorized as PK-2 (controlled risk) in 2022 and 2024, while it increased to PK-3 (moderate risk) in 2023. This escalation was primarily driven by a decline in risk management quality, particularly in operational, liquidity, and compliance risks. Conversely, legal and reputational risks consistently remained at a low level and were effectively managed. These findings suggest that fluctuations in inherent risk are not always accompanied by proportional improvements in risk management quality, thereby affecting the bank’s residual risk profile. Therefore, this study highlights the importance of implementing an integrated risk management system, such as Enterprise Risk Management (ERM) based on the COSO 2017 framework, supported by digital monitoring systems and enhanced human resource competencies, to ensure sustainable risk control and organizational performance.